Financial Performance Analysis At PT Indofood Sukses Makmur Tbk For The Period 2020-2024 - Isra' Indriyani; Nurman; Hety Budiyanti (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study analyzes the financial performance of PT Indofood Sukses Makmur Tbk during the period 2020-2024, a challenging era marked by the COVID-19 pandemic, inflation, exchange rate fluctuations, and dependency on commodity imports. The research objectives are to evaluate the company's overall financial health through comprehensive financial ratio analysis encompassing liquidity, solvency, activity, and profitability aspects, while integrating the influence of external macroeconomic factors on operational performance. This study employs a quantitative descriptive method with a case study approach, utilizing secondary data from annual financial reports and official sources including IDX, BI, and BPS. Financial ratio calculations are performed to evaluate year-to-year performance trends. The main findings reveal that PT Indofood demonstrated significant improvement across all financial dimensions: liquidity ratios increased from 1.37 to 2.15, indicating strong short-term debt servicing capability; solvency ratios improved with DAR declining from 0.51 to 0.46 and DER from 1.06 to 0.85, reflecting reduced dependency on external financing; profitability recovered with NPM reaching 7.5%, ROA 6.7%, and ROE 12.5% in 2024 after a temporary decline in 2022; and activity ratios remained stable with TATO ranging between 0.50-0.61 times, demonstrating efficient asset utilization. In conclusion, PT Indofood successfully navigated the pandemic challenges and volatile economic conditions through effective cost management, operational efficiency improvements, and prudent financial strategies, positioning the company for sustainable growth in the post-pandemic era.